Uji Sifat Fisik Ransum Ayam Broiler Bentuk Pellet yang Ditambahkan Perekat Onggok Melalui Proses Penyemprotan Air - Yuli Retnani; Nining Hasanah; Rahmayeni Rahmayeni; Lidy Herawati (Agricultural Faculty, 2010)
The physical characteristic test of broiler ration pelleted that added of onggok as binder with water spraying processABSTRACT. Pellet is a kind of solidified and mechanically compressed feed. Problem frequently rise is that pellet shape is easily damaged, brittle, and broken during production, transportation and storage processing. The purpose this study was to know the influence of onggok addition as binding agent with 5% water spraying on the physical characteristic of pellet form ration.The data were analyzed by analyzed of variance and the significant experiment results would be examined by orthogonal contrast test. The treatments consist from the first experiment were: A1 = basal ration + 0% spraying water, A2 = basal ration + 5% spraying water, A3 = basal ration + 10% spraying water and A4 = basal ration + 15% spraying water. The best result from the first experiment would be used for the second experiment, the treatments second experiment were: R1 = basal ration + 5% spraying water + 0% onggok, R2 = basal ration + 5% spraying water + 2% onggok, R3 = basal ration + 5% spraying water + 4% onggok and R4 = basal ration + 5% spraying water + 6% onggok.The parameters were water content, water activity, specific gravity, loose bulk density, compressed bulk density, angle of repose, modulus of fineness, average particle sizes and the durability of pellet form. The conclusion of the experiment that added of onggok as binder significant influenced of the characteristic physical pellet, i.e.: increased loose bulk density, compressed bulk density, modulus of fineness, average particle sizes, and durability of pellet, but decreased specific gravity, water content, angle of repose and water activity.